Perbandingan Efektivitas User Generated Content (UGC) dan Firm Generated Content (FGC) terhadap Brand Loyalty melalui Brand Trust pada Produk Yamaha NMAX di Instagram - Nega Avy Wicaksono; Ida Farida; Yohan Wismantoro; Guruh Taufan Hariyadi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of User Generated Content (UGC) and Firm Generated Content (FGC) on Brand Loyalty with Brand Trust as a mediating variable, while comparing the relative effectiveness of both types of content on the Yamaha NMAX product. A quantitative approach with an explanatory-comparative design was applied through a survey method on 145 respondents selected by purposive sampling from among active Yamaha NMAX users on Instagram. Data were analyzed using PLS-SEM assisted by SmartPLS. The test results revealed that UGC has a significant positive effect on Brand Trust, but is not proven to have a direct effect on Brand Loyalty. Conversely, FGC has a significant positive effect on both, both Brand Trust and Brand Loyalty. Brand Trust is also confirmed as a significant predictor of Brand Loyalty. The mediation analysis resulted in the finding that Brand Trust fully mediates the UGC path to Brand Loyalty, while partial mediation occurs in the FGC path. Comparatively, FGC has proven to be superior in driving Brand Trust and Brand Loyalty directly, while UGC contributes through indirect channels by first building consumer trust as a prerequisite for loyalty.